Evaluasi Kepuasan Masyarakat terhadap Program CSR Pengembangan Minat dan Bakat Anak Suku Buton oleh PT Pertamina Patra Niaga Fuel Terminal Samarinda - Febrianti Soleha; Rahmat Isya Ginanjar; Muhammad Iwan Setiawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to evaluate community satisfaction with the CSR Program of PT Pertamina Patra Niaga Fuel Terminal Samarinda focused on talent and interest development for children of the Butonese community in Sidodadi Urban Village. A quantitative approach was applied using the Community Satisfaction Index (IKM) survey instrument based on Ministerial Regulation PANRB No. 14 of 2017, supported by Importance Performance Analysis (IPA). Results indicate an IKM score of 84.18, which falls under the “very good” category. However, several priority attributes, such as scheduling accuracy and supporting infrastructure, require improvement. Recommendations include service quality enhancement, community engagement, and sustainability-based planning.